Allergic conjunctivitis: presentation, diagnosis, and management (Hong Kong Journal of Ophthalmology, 2008)
Allergic conjunctivitis is a common ocular eye disease in Hong Kong. Severe allergic eye disease can cause per- manent visual impairment if it is not managed appro- priately. In this overview of the condition, the clinical presentation, diagnosis, and current management strat- egy will be discussed.